Quantification of finite-temperature effects on adsorption geometries of π-conjugated molecules: azobenzene/Ag(111) - Mercurio, Giuseppe; Maurer, R. J.; Liu, W.; Hagen, S.; Leyssner, F.; Tegeder, Petra; Meyer, J.; Tkatchenko, A.; Soubatch, S.; Reuter, K.; Tautz, F. S. (Physical review. B, Condensed matter and materials physics, 2013)
The adsorption structure of the molecular switch azobenzene on Ag(111) is investigated by a combination of normal incidence x-ray standing waves and dispersion-corrected density functional theory. The inclusion of nonlocal collective substrate response (screening) in the dispersion correction improves the description of dense monolayers of azobenzene, which exhibit a substantial torsion of the molecule. Nevertheless, for a quantitative agreement with experiment explicit consideration of the effect of vibrational mode anharmonicity on the adsorption geometry is crucial.
Gesehen am 20.05.2021